DAKWAH ONLINE DAN TRANSFORMASI KEHIDUPAN BERAGAMA : STUDI KASUS DI KELURAHAN SUKARAJA KECAMATAN MEDAN MAIMUN - Utami, Fadma; Harahap, Elly Warnisyah; Fitriani, Fitriani (Studia Sosia Religia, 2025)
This study aims to analyze the impact of online da'wah on the religious life of the community in Sukaraja Subdistrict, Medan Maimun, in the aftermath of the Covid-19 pandemic. The phenomenon reflects a shift in community preferences for acquiring religious knowledge, from traditional sermons to social media as the primary source of religious information. The research focuses on the extent to which online da'wah influences the understanding and practice of religion among local residents. This study employs a descriptive qualitative method with a phenomenological approach to religion. It is a field research utilizing in-depth interviews, documentation, and analysis of articles relevant to online da'wah. The collected data is analyzed to understand how the community uses social media in their religious lives. The findings indicate that online da'wah has a significant impact on the religious life of the Sukaraja community. People find it easier to understand religious teachings through online media compared to traditional sermons like mass gatherings. The positive effects of online da'wah include improved understanding of previously unclear worship practices, reduced engagement in negative behaviors such as gossiping, and increased interest in sharing da'wah content such as videos, motivational quotes, Qur’anic verses, and hadiths. However, the use of online da'wah must remain grounded in the Qur’an and Hadith and must avoid provocation or hate speech. The study concludes that online da'wah plays a major role in supporting the community’s understanding and practice of religion, particularly by providing accessible and relevant alternative learning sources for the modern society.